High-fat and combined high-fat and sucrose diets promote cardiac oxidative stress independent of Nox2 redox regulation and obesity in rats - Gasparini, Patrícia Vasconcelos Fontana; Matias, Amanda Martins; Torezani-Sales, Suellem; Kobi, Jéssika Butcovsky Botto Sarter; Siqueira, Juliana Silva [UNESP]; Corrêa, Camila Renata [UNESP]; Leopoldo, Ana Paula Lima; Leopoldo, André Soares (Cell Physiol Biochem Press, 2021)
Background/Aims: Oxidative stress is associated with cardiometabolic alterations, and the involvement of excess glucose and fatty acids has been demonstrated in this process. Thus, the aim of this study was to investigate the effects of different hypercaloric diets on cardiac oxidative stress. Methods: Wistar rats were randomized into four groups: control (C), high-sucrose (HS), high-fat (HF), and high-fat with sucrose (HFS). Nutritional assessment, food profiles, histological analysis, comorbidities, and cardiovascular characteristics were determined. Cardiac oxidative stress was analyzed by malondialdehyde (MDA) and carbonylated proteins, and the cardiac protein expression levels of type 1 angiotensin receptor (AT-1), nicotinamide adenine dinucleotide phosphate oxidase 2 (Nox2), superoxide dismutase (SOD 1 e 2), glutathione peroxidase (GPX), and catalase (CAT) were determined by western blot. Results: The HF group showed an increase in adiposity; however, it did not present adipocyte hypertrophy and comorbidities. Cardiac MDA and carbonylated protein levels were higher in the HF and HFS compared with the C group. The levels of oxidant and antioxidant proteins showed no difference between the groups. Conclusion: HF and HFS dietary interventions promoted cardiac oxidative stress, in the presence and absence of obesity, respectively. However, this process was neither mediated by the pro-oxidants AT1 and Nox2, nor by the quantitative reduction of antioxidant enzymes.
Keywords: 1 angiotensin receptor; Cardiac; Hypercaloric diets; Nox2; Oxidative stress